2004
DOI: 10.1196/annals.1337.010
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Nonislet Autoimmunity: Comparison of Korean and U.S. Patients with Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) is frequently associated with other autoimmune diseases. The occurrence of common features of autoimmune diseases and the coassociation of multiple autoimmune diseases in the same individual or family support the notion that there may be common genetic factors. We previously reported that immunogenetic markers of T1D were similar in Korean and U.S. families. We hypothesized that nonislet autoimmunity might be expressed in a similar manner in Korean as well as in Caucasian patients and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(14 reference statements)
1
2
0
Order By: Relevance
“…Multinomial regression analysis revealed a positive association of the haplotype DRB1*040101/DQB1*0302 with altered anti-IA-2 titers in our population. These results are concordant with previous studies on Canadian (24), Japanese (20), German (10), Finnish (27,28), Italian (13), and Belgian (5) populations that showed that the prevalence and level of IA-2 autoantibody are increased in patients with HLA DR4/DQ8. However, IA-2 was negatively associated with DRB1*110101/ DQB1*030101 in titers and in prevalence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Multinomial regression analysis revealed a positive association of the haplotype DRB1*040101/DQB1*0302 with altered anti-IA-2 titers in our population. These results are concordant with previous studies on Canadian (24), Japanese (20), German (10), Finnish (27,28), Italian (13), and Belgian (5) populations that showed that the prevalence and level of IA-2 autoantibody are increased in patients with HLA DR4/DQ8. However, IA-2 was negatively associated with DRB1*110101/ DQB1*030101 in titers and in prevalence.…”
Section: Discussionsupporting
confidence: 92%
“…GAD and IA-2 are two of the major and bestcharacterized autoantigens. Several studies have demonstrated that HLA-DQ and -DR alleles influence T1D susceptibility (1,20,21,29), and T1D-predisposing or -protective HLA-DQ and -DR alleles were identified (1,29). Apart from the regulation of the autoreactive T cell repertoire by susceptible and protective HLA molecules, presentation of autoantigenic peptides by specific HLA molecules or induction of regulatory T cells (Treg) explains, at least in part, the modulatory capacity of HLA variants on the overall T1D risk (8).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact nature of autoimmunity of thyroid has not been fully elucidated, there is a wealth of evidence that AITDs develop in genetically susceptible individuals, in conjunction with environmental triggers [4]. λs, an indicator of familial aggregation, has been reported to be between 5.9 and more than 10 in AITDs, suggesting a strong genetic component in the development of the disease [5].…”
Section: Introductionmentioning
confidence: 99%